Uncovering Spiritual Narratives : Using Story in Pastoral Care and Ministry - Coyle, Suzanne M. (Book collections on Project MUSE., 2014)
All cultures use story as a way to make sense of life experiences. Yet for many, particularly in the western world, only a single story line is seen as the "real truth." Using narrative therapy as a caregiving approach can help individuals uncover multilayered narratives that are far more complex and liberating. Coyle contends that not only are these more complex narratives more helpful in giving our lives meaning, they also critique the cultural discourses in which they arose. Drawing on both theological approaches and real life experiences, Coyle creates a contextual pastoral theology that helps caregivers find the power of God in people's stories.